Comparison of the dynamical response of low latitude middle atmosphere to the major stratospheric warming events in the Northern and Southern Hemispheres. (August 2016) - Bhagavathiammal, G.J.; Sathishkumar, S.; Sridharan, S.; Gurubaran, S.
Abstract: This study presents comparison of low-latitude dynamical responses to boreal 2008/09 and austral 2002 winter Major Stratospheric Warming (MSW) events, as both events are of vortex split type. During these winters, planetary wave (PW) variability and changes in low-latitude circulation are examined using European Center for Medium Range Weather Forecasting (ECMWF) reanalysis (ERA)-interim data sets and mesospheric wind data acquired by the MF radars at Tirunelveli (8.7°N) and Rarotonga (22°S). Eliassen-Palm diagnostic is used to provide an evidence for the lateral PW energy propagation from high to low-latitudes during both the MSW events. The PW flux reaches much lower latitudes during the boreal event than during the austral event. The low-latitude westward winds at stratospheric heights are stronger (weaker) during the boreal (austral) MSW. Weak (strong) PW wave activity at low latitude mesospheric heights during boreal (austral) MSW indicates the influence of low-latitude stratospheric westward winds on the vertical propagation of PW to low-latitude mesosphere. Highlights: MSW of boreal winter 2008/09: comparison with austral winter 2002. Low latitude circulation changes in association with high latitude during MSW. PW energy propagates to lower latitude during boreal not in austral winter. Low latitude stratospheric winds influence PW activity at low latitude MLT. Variability in PW activity prior-post MSW from Tirunelveli and Rarotonga MLT winds.